Hybrid approach for container terminals performances evaluation and analysis. (1st January 2014) - Nicoletti, Letizia; Chiurco, Alessandro; Arango, Carlos; Diaz, Rafael
Turnaround time, defined as the total time spent by a vessel within the port area, is one of the most important key performance measures for a container terminal. In this paper, the authors propose a hybrid approach based on simulation and genetic algorithms to investigate vessels' turnaround time in a real container terminal under different scenarios characterised by increases in containers traffic and vessels traffic. The authors show how a modular simulation model integrated with optimisation algorithms can be used as an advanced support tool to identify resources capacity constraints and to identify how such constraints affect the vessels' turnaround time.